Pregnancy during COVID 19 pandemic associated with differential gut microbiome composition as compared to pre-pandemic - Therese A. Rajasekera; Jeffrey D. Galley; Lauren Mashburn-Warren; Christian L. Lauber; Michael T. Bailey; Brett L. Worly; Tamar L. Gur (Scientific Reports)
Abstract The first two years of the COVID-19 pandemic and subsequent health mandates resulted in significant disruptions to daily life, creating a period of heightened psychosocial stress in myriad aspects. Understanding the impact of this period on pregnant individuals’ bacteriomes is crucial as pregnancy is a period of heightened vulnerability to stress and its sequelae, anxiety and mood disorders, which have been demonstrated to alter gut microbiome composition. In a prospective cohort study (N = 12–26) conducted from February 2019 to August 2021, we examined psychometric responses and rectal microbiome swabs from pregnant individuals. Full-length 16 S rRNA sequencing followed by calculation of diversity metrics and relative abundance values were used to interrogate fecal microbiome community composition across pandemic groups. Distinct shifts in bacterial diversity and composition were observed during early to late pregnancy in the pandemic group, including lower relative abundance of pathogenic and lesser-known taxa. However, distribution of stress and depressive symptoms did not significantly differ from the pre-pandemic period while the correlation between stress and depressive symptoms dissipated during the pandemic. Our findings suggest that living through the COVID-19 pandemic altered the gut microbiome of pregnant individuals, independent of perceived stress.